Therapeutic Potential of Clove Essential Oil in Diabetes: Modulation of Pro‐Inflammatory Mediators, Oxidative Stress and Metabolic Enzyme Activities. Issue 3 (23rd February 2023) - Nait Irahal, Imane; Darif, Dounia; Guenaou, Ismail; Hmimid, Fouzia; azzahra Lahlou, Fatima; Ez‐zahra Ousaid, Fatima; Abdou‐Allah, Fatima; Aitsi, Lamiaa; Akarid, Khadija; Bourhim, Noureddine
Abstract: Type 1 diabetes is characterized by insulin deficiency due to the destruction of pancreatic β cells, leading to hyperglycemia, which in turn induces vascular complications. In the current study, we investigated the effect of intraperitoneal administration of clove essential oil (CEO: 20 mg/kg body weight) on certain oxidative stress and glucose metabolism enzymes, as well as the expression of proinflammatory mediators. Administration of CEO to diabetic rats showed a significant decline in blood glucose levels, total cholesterol, and xanthine oxidase, compared to the streptozotocin group. Furthermore, these treated rats elicited a notable attenuation in the levels of lipid peroxides, and thiols groups in both liver and brain tissues. The activities of antioxidant and metabolic enzymes were reverted to normality in diabetic upon CEO administration. In addition to its protective effects on red blood cell hemolysis, CEO is a potent α‐amylase inhibitor with an IC50 =298.0±2.75 μg/mL. Also, treatment of diabetic rats with CEO significantly reduced the iNOS expression in the spleen. Our data showed that CEO has potential beneficial effects on diabetes, which can possibly prevent the pathogenesis of diabetic micro‐ and macrovascular complications. Abstract :